-3r+3=-24

Simple and best practice solution for -3r+3=-24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3r+3=-24 equation:



-3r+3=-24
We move all terms to the left:
-3r+3-(-24)=0
We add all the numbers together, and all the variables
-3r+27=0
We move all terms containing r to the left, all other terms to the right
-3r=-27
r=-27/-3
r=+9

See similar equations:

| 184=2m+7(4m-8) | | 7(4k-7)+6=-267 | | 88=2(2-6n) | | 2h2-5h-12=0 | | -6(5x-4)=-216 | | 2-3(5v-3)=-94 | | 6x-5x=18 | | -2-4(1+8n)=-102 | | 12x+15=12-10x+12 | | 7+4n+1=-8 | | -(3x-5)-(5x-6)+8=-5(x-1)-(7x+5)+3 | | 6x-15x=x-20 | | 3k=2.4 | | 6x-15x=x—20 | | 7m/5=3 | | (15b-2)-7(2b+4)=-4 | | M-34/6-7m-21/5=1 | | x=3E-08(4532951+0.0019 | | |x+1|+|x-1|=2x | | 4(x+7=3(x-8)+x | | -17-4x=-5-5(1×5x) | | x-71=89 | | 5(x+3)+8=5x+8 | | 3^(3x-3)=36 | | n(n-3)=20 | | -2(6y-7)-y=-2(y-3) | | -4(4y-8)-y=-2(y-5) | | 9x-3x+6=x-4+10 | | m+8=34 | | 5/2a-12=1/3a+1 | | 3p+p=120 | | 7(t-5)+5t=6(2t+3)-10 |

Equations solver categories